2013
DOI: 10.1249/mss.0b013e3182699239
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome and Daily Ambulation in Children, Adolescents, and Young Adults

Abstract: Purposes To compare daily ambulatory measures in children, adolescents, and young adults with and without metabolic syndrome, and to assess which metabolic syndrome components, demographic measures, and body composition measures are associated with daily ambulatory measures. Methods Two-hundred fifty subjects between the ages of 10 and 30 years were assessed on metabolic syndrome components, demographic and clinical measures, body fat percentage, and daily ambulatory strides, durations, and cadences during s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
(57 reference statements)
1
9
0
1
Order By: Relevance
“…We reported negative associations between each of the peak cadence indicators studied and both BMI and BF%. Similarly Gardner et al 16 reported sex-adjusted differences in daily average cadence related to presence or absence of metabolic syndrome (14.9 versus 13.6 steps/min) in children, adolescents, and young adults. The lower values for peak cadence indicators in obese children should also be related to lower daily energy expenditure of physical activity 39 , setting the stage for long-term positive energy balance and exacerbating further increases in body weight and fatness.…”
Section: Bmi-defined Weight Status Samplementioning
confidence: 84%
See 3 more Smart Citations
“…We reported negative associations between each of the peak cadence indicators studied and both BMI and BF%. Similarly Gardner et al 16 reported sex-adjusted differences in daily average cadence related to presence or absence of metabolic syndrome (14.9 versus 13.6 steps/min) in children, adolescents, and young adults. The lower values for peak cadence indicators in obese children should also be related to lower daily energy expenditure of physical activity 39 , setting the stage for long-term positive energy balance and exacerbating further increases in body weight and fatness.…”
Section: Bmi-defined Weight Status Samplementioning
confidence: 84%
“…A recent review has introduced the concept of using cadence as a way to study free-living ambulatory behavior 14 . Some studies have used accelerometer step counts to not only describe the total amount of daily ambulation but also different aspects of children's cadence [15][16][17] . In addition to analyzing cadence to describe movement it is also possible to measure and analyze patterns of peak cadence for different time increments.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The counts per minute monitored by an accelerometer have shown significant correlations with energy expenditure in various physical activities in children (Mattocks et al, 2007). There have been studies using accelerometers to evaluate PA in both US and European children, with the average measuring period lasting 3 to 7 days (Brage et al, 2004;Dencker et al, 2010;Gradner et al, 2013;Stone et al, 2009), but few data on objectively measured PA levels of Chinese children are available. Therefore, with the aim of studying whether daily PA levels display a correlation with the components of childhood MS, we conducted this study in Tianjin, a large city in North China.…”
Section: Introductionmentioning
confidence: 99%